Field-Emission Study of Multi-Walled Carbon Nanotubes Grown On Si Substrate by Low Pressure Chemical Vapor Deposition - J. Ali; A. Kumar; S. Husain; S. Parveen; M. Husain (Журнал нано- та електронної фізики)
CNTs are synthesized by Low Pressure Chemical Vapor Deposition (LPCVD) method at 600 °C. The Si substrate is coated with Fe, used as a catalyst, by RF- sputtering. The thickness of the catalyst film is measured to be approximately 15 nm. Three precursor gases Acetylene (C2H2), Ammonia (NH3) and Hydrogen (H2) with flow rates 15 sccm, 100 sccm and 100 sccm respectively are allowed to flow through the tube reactor for 20 minutes. The as grown CNTs sample was characterized by Scanning Electron Microscope (SEM). SEM images show that the diameter of as grown CNTs is in the range of 20-50 nm. Field emission properties of as grown sample have also been studied. The CNTs film shows good field emission with turn on field Eα = 2.10 V/μm at the current density of 4.59 mA/cm2 with enhancement factor β = 1.37 × 102.